A method for manufacturing a dense layer that can be used as an electrode and / or electrolyte for lithium-ion batteries, and a lithium-ion microbattery obtained by this method.

JP7943812B2Active Publication Date: 2026-10-30I TEN
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022559538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-03-30
Publication Date
2026-10-30
Estimated Expiration
2041-03-30

Smart Images

  • Figure 0007943812000001
    Figure 0007943812000001
  • Figure 0007943812000002
    Figure 0007943812000002
  • Figure 0007943812000003
    Figure 0007943812000003
Patent Text Reader

Abstract

1. A method for producing a densified layer, comprising the steps of: providing a substrate and a suspension of unagglomerated nanoparticles of material P; depositing a layer on the substrate using the suspension of primary nanoparticles of material P; drying the obtained layer; densifying the dried layer by mechanical compression and / or heat treatment; the method further comprising: providing a suspension of unagglomerated nanoparticles of material P comprising nanoparticles of material P having a size distribution, the size distribution being determined by the D 50 and characterized in that: nanoparticles of a material P having a first size D1 of said size distribution between 20 nm and 50 nm and a D1 at least 5 times smaller than the value of D1. 50 and nanoparticles of material P of a second size D2 characterized by a value of D ≈ 1 / 2; or the size distribution is such that the nanoparticles of material P have an average size of less than 50 nm and a ratio of the standard deviation to the average size is greater than 0.6.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to the production of dense layers suitable for use in electrochemical devices, particularly as electrode or electrolyte layers. These layers can be used in multilayer batteries, such as lithium-ion microbatteries. They are manufactured from inorganic nanoparticles and may be functionalized with layers of organic coatings, which may be polymers, as needed.

[0002] The present invention also relates to a novel method for producing these dense layers from nanoparticles, and to layers obtained by this method and to multilayer microbatteries incorporating at least one of the layers obtained by this method.

[0003] The present invention also relates to a novel method for manufacturing a lithium-ion battery, wherein at least one dense electrode layer is deposited using a novel method for manufacturing a dense layer, and a porous layer is also deposited. [Background technology]

[0004] Lithium-ion batteries have the highest energy density among the various electrochemical energy storage technologies proposed. Electrodes for manufacturing lithium-ion batteries have a variety of structures and chemical compositions. Methods for manufacturing lithium-ion batteries are described in numerous papers and patents, and an overview is provided in the 2002 publication "Advances in Lithium-Ion Batteries" (W. van Schalkwijk and B. Scrosati) (Kluever Academic / Plenum Publishers).

[0005] There is a growing need for microbatteries, which are extremely small, rechargeable batteries that can be embedded in electronic cards; these electronic circuits can be used in a variety of fields, including cards for protecting transactions, electronic tags, implantable medical devices, and various micromechanical systems.

[0006] According to conventional techniques, electrodes for lithium-ion batteries can be fabricated using coating techniques (particularly: roll coating, doctor blade coating, tape casting, and slot die coating). In these methods, the active material that helps in manufacturing the electrodes is in the form of a powder with an average particle size of 5 to 15 μm in diameter. These particles are incorporated into an ink formed from these particles and deposited on the surface of a substrate.

[0007] These technologies enable the fabrication of layers with thicknesses ranging from approximately 50 μm to 400 μm. The output and energy of the battery can be adjusted depending on the layer thickness, its porosity, and the size of the active material particles. Thinner thicknesses are required to manufacture microbatteries.

[0008] The ink (or paste) deposited to fabricate the electrodes contains not only active material particles but also a (organic) binder, carbon powder to provide electrical contact between particles, and a solvent to be evaporated during the electrode drying process. A calendering process is performed on the electrodes to improve the quality of the electrical contact between particles and to compress the deposited layer. After this compression process, the active material particles of the electrodes occupy approximately 60% of the volume of the deposit, which generally means that there is a porosity of 40% between the particles.

[0009] The contact between each particle is essentially point-like, and the electrode structure is porous. The porosity is filled with an electrolyte, which can be in the form of a liquid (an aprotic solvent in which the lithium salt is dissolved) or a more or less polymerized gel impregnated with the lithium salt. The thickness of electrodes for lithium-ion batteries is generally 50 μm to 400 μm, and lithium ions are transported in the thickness direction of the electrode through the porous structure filled with the electrolyte (containing the lithium salt). Depending on the amount and size of the pores, the diffusion rate of lithium at the electrode thickness changes.

[0010] To ensure proper battery operation, lithium ions need to diffuse through both the particle thickness and the electrode thickness. Diffusion of the active material within the particles is slower than diffusion within the electrolyte impregnating the porous electrode: this electrolyte is liquid or gel-like. The slow diffusion within the electrode particles results in a high series resistance in the battery. Furthermore, to achieve sufficient battery power, the particle size needs to be small; in standard lithium-ion batteries, this is typically 5μm to 15μm.

[0011] Furthermore, the power and energy of a battery can be adjusted depending on the thickness of the layer and the size and density of the active material particles contained in the ink. Energy density inevitably increases, while power density is reduced. High-power battery cells require the use of thin, highly porous electrodes and separators, but to increase energy density, these same thicknesses must be increased to decrease porosity. John Newman's article, "Optimization of Porosity and Thickness of a Battery Electrode by Means of a Reaction-Zone Model," J. Electrochem. Soc., Vol. 142, No. 1, January 1995, demonstrates the respective effects of electrode thickness and its porosity on discharge rate (power) and energy density.

[0012] However, increasing the porosity of the electrodes tends to decrease the energy density of the battery; to increase the energy density of the electrodes, the porosity must be reduced. In current lithium-ion batteries, the porosity filled with electrolyte located between the active material particles is essentially what allows lithium ions to diffuse within the electrodes. If there is no electrolyte-filled porosity, lithium ions are transported from one particle to another at contact between particles, and this contact is essentially in the form of a point. Therefore, the lithium ion transport resistance is so high that the battery cannot function.

[0013] Furthermore, for proper functioning, the pores of the electrodes must be filled with electrolyte. This filling is only possible if these pores are open. Moreover, depending on the size and curvature of the pores, it can be very difficult, or even impossible, to impregnate the electrodes with electrolyte. As the porosity of the electrolyte-impregnated pores decreases, the electrical resistance of the layer decreases and its ionic resistance increases. When the porosity falls below 30% or 20%, some pores can close again, significantly increasing the ionic resistance and preventing the electrodes from wetting with the electrolyte.

[0014] Therefore, in order to fabricate a poreless electrode film in order to increase energy density, the film thickness must be 50 μm or less, preferably 25 μm or less, in order to rapidly diffuse lithium ions in the solid without reducing power.

[0015] The main process used to manufacture dense films is the vacuum deposition of lithium-ion-inserted electrode material. This technique makes it possible to obtain dense films that are free from porosity and binders, resulting in satisfactory temperature behavior with excellent energy density.

[0016] The absence of porosity allows for the transport of lithium ions by diffusion across the membrane, without the need to use polymers containing lithium salts or organic electrolytes based on solvents.

[0017] Such a complete inorganic film offers superior performance in terms of aging, safety, and temperature behavior.

[0018] PVD (Physical Vapor Deposition) is currently the most commonly used technique for manufacturing thin-film microbatteries. In fact, these products require films free of porosity and other point defects to ensure the low electrical resistivity and proper ion conductivity necessary for the proper operation of electrochemical devices.

[0019] The deposition rates achieved with this technique are on the order of 0.1 μm to 1 μm per hour. PVD deposition technology yields very high-quality films that are virtually free of point defects and allows deposition at relatively low temperatures. However, due to differences in evaporation rates between different elements, it is difficult to deposit complex compounds and control the stoichiometry of the layers using such techniques. While this technique is perfectly suited for creating thin layers with simple chemical compositions, increasing the thickness of the deposit requires excessively long deposition times, making industrial applications in the field of low-cost products impractical.

[0020] Furthermore, the vacuum deposition technology used to manufacture such films is extremely expensive, making it difficult to implement industrially over large surface areas with high productivity.

[0021] Other techniques currently available for producing dense ceramic films include embodiments based on the densification of compact particle deposits, or embodiments that actually use sol-gel type techniques to obtain films. Sol-gel techniques consist of depositing a polymer lattice obtained after hydrolysis, polymerization, and condensation steps onto the surface of a substrate. The sol-gel transition occurs when the solvent that accelerates the reaction process on the surface evaporates. This technique makes it possible to produce very thin, compact deposits. Films thus obtained have a thickness of about 100 nanometers. These thicknesses are too small to provide adequate energy storage for battery applications.

[0022] Increasing the thickness of the deposit without creating a risk of cracking or fissure formation requires a series of steps. However, increasing the thickness of the layer reduces the industrial productivity of this technology.

[0023] Furthermore, it is also possible to manufacture ceramic electrodes and / or electrolyte membranes for batteries by powder sintering. For this purpose, a paste containing ceramic particles and an organic binder is arranged in a film-like manner to obtain a precursor strip, commonly known as a "green sheet."

[0024] Next, this precursor strip is fired to remove organic matter, and then sintered at a high temperature to obtain a sheet of ceramic material.

[0025] In this case, a metal film that helps collect current on these electrodes is also deposited using inking technology. The metal powder is sintered simultaneously with the "green sheet." In fact, during the sintering process, the pores between the particles of the ceramic material are filled, resulting in the strip shrinking.

[0026] By sintering the current collector with a ceramic film, it becomes possible to accommodate dimensional variations in the ceramic film and the metal current collector, thereby preventing the occurrence of cracks.

[0027] These methods are performed at very high temperatures. However, battery materials are generally temperature-sensitive and degrade rapidly when subjected to such heat treatment.

[0028] To lower this sintering temperature, the use of nanoparticles has been proposed. In this case, a compact deposit of unaggregated nanoparticles is generated. These deposits can be easily sintered at relatively low temperatures. This low temperature makes it possible to envision direct sintering on a metal substrate.

[0029] However, when these deposits form on a metal substrate, it has been observed that, depending on the thickness, compactness, and particle size of the deposit, they promote crack formation during the drying and / or sintering process.

[0030] Electrophoretic nanoparticle deposition techniques are used to increase the density of the deposit and facilitate low-temperature sintering with fewer cracks; this is described in several patent applications, for example, International Publication Nos. 2013 / 064773, 2013 / 064776, 2013 / 064777, and 2013 / 064779 (Fabien Gaben). Thermal aggregation is carried out at particularly low temperatures due to the small size of the nanoparticles, and is actually preferably less than 100 nm. [Overview of the project] [Problems that the invention aims to solve]

[0031] This invention aims to at least partially improve upon the shortcomings of the prior art described above.

[0032] More specifically, the problem that the present invention aims to solve is to provide a simple, safe, rapid, easy-to-implement, and inexpensive method for directly manufacturing a dense ceramic layer on a metal substrate.

[0033] Another objective of the present invention is to produce a dense solid (ceramic) layer suitable for lithium-ion microbatteries that is free from or contains very few defects or porosity.

[0034] Another object of the present invention is to provide dense electrodes and dense electrolytes having high ionic conductivity, a stable mechanical structure, good thermal stability, and a long service life.

[0035] A further object of the present invention is to provide a method for manufacturing electronic, electrical, or electrotechnical devices such as microbatteries, capacitors, supercapacitors, and photocells containing dense electrodes or dense electrolytes according to the present invention. [Means for solving the problem]

[0036] According to the present invention, this problem is solved by a method for manufacturing a dense layer, which includes the following steps: - A step of supplying a suspension of non-aggregated nanoparticles of the substrate and material P; - A step of depositing a layer on the substrate using a suspension of primary nanoparticles of the material P; - A step of drying the obtained layer; - A step of densifying the dried layer by mechanical compression and / or heat treatment; It is known that the drying process and the densification process can be performed at least partially simultaneously, or during the temperature rise.

[0037] The method forming the first objective of the present invention is characterized in that a suspension of unaggregated nanoparticles of material P comprises nanoparticles of material P having a specific size distribution, and enables obtaining a density greater than 75% after deposition. The size is its D 50 Characterized by values.

[0038] This particle size distribution can be obtained in one of the following ways: -Continuously: In this case, the ratio of the standard deviation / average size of the nanoparticles of material P must be greater than 0.6, and the average size of the primary nanoparticles of material P must be 50 nm or less; or -Discontinuously: In this case, the size distribution of nanoparticles in material P includes first-size D1 nanoparticles ranging from 50 nm to 20 nm, and second-size D2 nanoparticles that are at least one-fifth the size of D1. Very favorably, the particles of size D1 account for 50% to 75% of the total mass of the nanoparticles.

[0039] A suspension of non-aggregated nanoparticles of material P can be obtained using a monodisperse suspension of size D1, and / or a suspension of nanoparticles of size D2 can be obtained using a monodisperse suspension.

[0040] According to the present invention, the deposition of a solid, dense ceramic layer is carried out by electrophoresis, dip coating, inkjet printing, roll coating, slot die coating, curtain coating, or doctor blade.

[0041] After deposition, the dried layer has a density greater than 75% due to the particle size distribution of its constituent nanoparticles. This density can be further increased by a process of densifying the dried layer by mechanical compression and / or heat treatment.

[0042] A second object of the present invention is a dense layer that can be obtained by the method according to the first object. In particular, it can be selected from an anode, cathode and / or electrolyte for a lithium-ion battery.

[0043] A third object of the present invention is a dense layer in electrochemical, electronic, electrical, or electrotechnical devices such as batteries (preferably lithium-ion batteries), capacitors, supercapacitors, capacitances, resistors, induction coils, and transistors, the dense layer of which can be obtained by the method according to the present invention. The dense layer of which may be an anode layer, a cathode layer, and / or an electrolyte layer.

[0044] A fourth object of the present invention is a method for manufacturing a dense layer in a lithium-ion battery, wherein the method has the characteristics of the above-described method for manufacturing a dense layer, and all embodiments can be carried out for manufacturing a dense layer in a lithium-ion battery.

[0045] The ultimate object of the present invention is an electrochemical device, in particular a microbattery, in particular a lithium-ion microbattery, comprising at least one dense layer according to the second object of the present invention.

[0046] In one embodiment, the lithium-ion microbattery includes an anode and a cathode which are dense layers according to the present invention. The anode and / or cathode may have a thickness of about 1 μm to about 50 μm.

[0047] In the first modified example, the electrolyte layer may also be a dense layer according to the present invention. In the second modified example, the microbattery includes a liquid electrolyte permeated into a porous separator that separates the anode and the cathode. It is advantageous that this electrolyte layer or separator has a thickness of about 1 μm to about 20 μm, preferably about 3 μm to about 10 μm.

[0048] In a further embodiment, only the electrolyte layer is the dense layer according to the present invention. [Modes for carrying out the invention]

[0049] 1.Definition Within the scope of this specification, particle size is defined by its maximum dimension. The term “nanoparticle” refers to any particle or object of nanometer size whose at least one dimension is 100 nm or less. This size D is here defined as size D 50 It is written as follows.

[0050] The term "nanoparticles" is used here to refer to primary particles, as opposed to particles formed by the aggregation or clumping of several primary particles. Such clumps can be reduced to nanoparticles (in the sense understood here) by dispersion operations such as grinding or sonication.

[0051] The density of the layer is expressed here as a relative value (e.g., a percentage), and the actual density of the layer (here, d layer (Assuming) and the theoretical density of the constituent solid material (here, d theoretical This is obtained by comparing (assuming the following). Therefore, the porosity of the layer, expressed as a percentage, is determined as follows:

number

[0052] Within the scope of this specification, an electronic insulating material or layer, preferably an ion conductive layer, has an electrical resistivity (resistance to the flow of electrons) of 10. 5 It is a material or layer with a density greater than Ω·cm. The term "ionic liquid" refers to any liquid salt that can conduct electricity and is distinguished from all molten salts by its melting point below 100°C. Some of these salts remain liquid at ambient temperature and do not solidify even at very low temperatures. Such salts are called "ionic liquids at room temperature."

[0053] The term "mesoporous" material refers to any solid having pores in its structure that are intermediate in size between micropores (less than 2 nm wide) and macropores (greater than 50 nm wide), i.e., pores between 2 nm and 50 nm wide, called "mesopores." This term is consistent with the terminology adopted by IUPAC (International Union of Pure and Applied Chemistry) as a reference for those skilled in the art. Therefore, the term "nanopore" is not used here, although mesopores, as defined above, have dimensions in nanometers according to the definition of nanoparticles. Pores smaller than the size of mesopores are known to those skilled in the art as "micropores."

[0054] An overview of the concept of porosity (and the terms disclosed above) is provided in "Texture des materiaux pulverulents ou poreux" by F. Rouquerol et al., published on page 1050 of the "Techniques de l'Ingenieur", Analysis and Characterisation paper; this article describes techniques for identifying porosity, particularly the BET method.

[0055] In the present invention, the term "mesoporous layer" refers to a layer having mesopores. As will be explained below, in these layers, mesopores contribute significantly to the total porous volume; this fact is referred to in the expression "mesoporous layer with a porosity greater than X%" used in the following description, where X% is preferably 25% or more, more preferably 30% or more, and even more preferably 30-50% of the total volume of the layer.

[0056] The term "aggregate," according to the IUPAC definition, refers to a collection of weakly bound primary particles. In this case, these primary particles are nanoparticles with a diameter that can be measured by a transmission electron microscope. Typically, according to the art known to those skilled in the art, aggregates of aggregated primary nanoparticles can be suspended in a liquid phase and broken down (i.e., into primary nanoparticles) under the influence of ultrasound.

[0057] According to the IUPAC definition, the term "clump" refers to a collection of primary particles or aggregates that are strongly bound together.

[0058] According to the present invention, the term “electrolyte layer” refers to a layer within an electrochemical device, which can operate according to its end-use. The electrolyte layer is an ionic conductor but an electrically insulator. For example, if the electrochemical device is a lithium-ion secondary battery, the term “electrolyte layer” refers to either a dense electrolyte layer on which lithium cations migrate, or a “porous inorganic layer” impregnated with a lithium-supported phase. The porous inorganic layer in the electrochemical device is also referred to here as a “separator” according to terminology used by those skilled in the art.

[0059] 2. Detailed explanation According to the present invention, this problem is solved by a method of depositing a layer using a nanoparticle suspension in which the nanoparticles have a specific type of particle size distribution.

[0060] According to one essential aspect of the present invention, a nanoparticle suspension representing a specific nanoparticle size distribution is used in a manner that significantly increases the deposition density of nanoparticles before sintering.

[0061] Obtaining the most compact deposit possible before sintering reduces the risk of shrinkage and cracking. To achieve the most compact deposit, it is necessary not only to perfectly control the size distribution of nanoparticles, but also to ensure that these nanoparticles are deposited in the most compact manner without aggregating.

[0062] To obtain such compact deposits, either electrophoretic deposition techniques for dilute suspensions or actual deposition techniques for concentrated suspensions of these polydisperse nanoparticles that do not aggregate can be used, such as inking, dip coating, curtain coating, doctor blade, or slot die. To obtain such concentrated suspensions, stabilizers, which are organic ligands (e.g., PVP type), must be used to prevent aggregation between nanoparticles. These ligands are removed at the start of the sintering heat treatment: typically, an intermediate heat lamp is completed to remove all of these organic compounds before sintering.

[0063] The viscosity of a suspension used for deposition fundamentally depends on the properties of the liquid phase (solvent), the particle size, and its concentration (expressed as a dry extract). The viscosity of the suspension and the parameters of the deposition method (particularly the migration or passage rate in the liquid) determine the thickness of the deposition. Depending on these parameters specific to the deposition technique, the viscosities commonly used for dip coating, curtain coating, or slot die coating can vary considerably, ranging from approximately 20 cP to approximately 2000 cP when measured at 20°C. Colloidal suspensions intended for deposition are often referred to as "inks," regardless of their viscosity.

[0064] Once these organic compounds are removed, the nanoparticles come into contact, initiating the solidification process. The surfaces of the nanoparticles are welded together at the contact points; this phenomenon is known as "necking" (neck formation). During sintering, these welded contact points increase by diffusion, filling the voids left by the pores during the initial deposition. Filling these voids is the cause of shrinkage.

[0065] Furthermore, in order to ultimately obtain a porosity of less than 15%, preferably less than 10%, in thick deposits formed on crack-free metal substrates, it is necessary to maximize the compactness of the initial nanoparticle deposits while maintaining the nanometer effect, which allows for lowering the solidification temperature to maintain compatibility with the use of metal substrates.

[0066] According to the present invention, a colloidal nanoparticle suspension in which the average nanoparticle diameter does not exceed 100 nm is used. Furthermore, these nanoparticles have a relatively wide size distribution. When this size distribution is approximately a normal distribution, the ratio of the standard deviation to the average radius of the nanoparticles (σ / R) mean ) must be greater than 0.6.

[0067] To enhance the compactness of the initial deposit before sintering, it is also possible to use a mixture of two nanoparticle size groups. In this case, the average diameter of the maximum distribution should not exceed 100 nm, preferably not exceeding 50 nm. This first group of the largest nanoparticles is σ / R mean It may have a narrow size distribution with a ratio of less than 0.6. This "large" nanoparticle population should account for 50% to 75% of the dry extract of the deposition (expressed as a mass % of the total mass of nanoparticles in the deposit). As a result, the second population of nanoparticles accounts for 50% to 25% of the dry extract of the deposit (expressed as a mass % of the total mass of nanoparticles in the deposit). The average diameter of the particles in this second population must be at least 5 times smaller than the average diameter of the largest nanoparticle population. With respect to the largest nanoparticles, the size distribution of this second population is even narrower, σ / R mean The ratio may be less than 0.6. The average diameter of the second population is preferably at least 1 / 15, preferably at least 1 / 12, of the largest nanoparticle population; this promotes densification of the layer after deposition.

[0068] In any case, the two groups must exhibit aggregation in the resulting ink. Furthermore, these nanoparticles can be advantageously synthesized in the presence of ligands or organic stabilizers to prevent aggregation or clumping of the nanoparticles.

[0069] The preparation of colloidal suspensions by wet nano-grinding allows for a relatively wide size distribution. However, depending on the properties of the ground material, its "brittleness," and the reduction coefficient applied, the primary nanoparticles may be damaged or amorphous.

[0070] The materials used in the manufacture of lithium-ion batteries are particularly sensitive, and even slight changes in their crystalline state or chemical composition can lead to a decrease in electrochemical performance. Furthermore, for this type of application, it is preferable to use nanoparticles prepared directly in suspension by precipitation according to methods such as solvothermal or hydrothermal processes, with the desired primary nanoparticle size.

[0071] These precipitation-based nanoparticle synthesis methods allow for the production of primary nanoparticles with a small and homogeneous size distribution, good crystallinity, and high purity. Using these methods, it is also possible to obtain extremely small particle sizes, potentially less than 10 nm, in a non-aggregated state. Therefore, to prevent the formation of clumps and aggregates during synthesis, it is necessary to directly add a ligand to the synthesis reactor. For example, PVP can be used to fulfill this function.

[0072] Because the size distribution of unaggregated nanoparticles obtained by precipitation is relatively narrow, a colloidal suspension preparation strategy that mixes the two size distributions according to the above rules is preferred to maximize the compactness of the deposit before sintering. This makes it possible to directly generate a relatively thick deposit on the metal substrate after sintering, and because the nanoparticle size used is small, the heat treatment of sintering can be maintained at a relatively low temperature, with little to no risk of cracking.

[0073] Next, the bimodal nanoparticle suspension is densified by low-temperature heat treatment and used to deposit compact layers suitable for use as electrodes or electrolytes in electrochemical devices, particularly lithium-ion batteries. Various methods can be used to deposit these layers, particularly printing methods selected from electrophoresis, inkjet printing, and flexographic printing, as well as coating methods preferably selected from doctor blade coating, roll coating, curtain coating, dip coating, and slot die coating. These methods are simple, safe, easy to implement, easy to industrialize, and ultimately allow for the acquisition of homogeneous, dense layers. Electrophoresis allows for the deposition of uniform layers at a fast deposition rate over a large surface area. Coating techniques, particularly dip coating, roll coating, curtain coating, or doctor blade coating, simplify the management of the solution bath in relation to electrophoresis because the composition of the bath is kept constant during deposition by coating. Inkjet printing allows for the production of localized deposition.

[0074] Using the above method with bimodal or polydispersible nanoparticle suspensions, thick, dense electrodes and electrolytes can be obtained in a single step.

[0075] The method according to the present invention makes it possible to produce a dense layer having a density of at least 90%, preferably at least 95%, more preferably at least 96%, and optimally at least 97% of the theoretical density, with the remainder consisting of residual pores consisting of closed pores.

[0076] Herein, an embodiment of the dense electrode according to the present invention will be described as a non-limiting example; this description will provide a more detailed explanation of specific details of the method according to the present invention.

[0077] Properties of current collectors In principle, the substrate functioning as the current collector of a battery using the dense electrode according to the present invention is a metal, for example a metal sheet. It must be selected to withstand the temperature of the heat treatment or thermomechanical treatment applied to the layers deposited on this substrate, which temperature depends on the chemical nature of said layers. The substrate is preferably selected from strips made of titanium, molybdenum, chromium, tungsten, copper, nickel, stainless steel, or any alloy comprising at least one of the aforementioned elements.

[0078] In principle, the metal sheet may in particular be coated with a layer of a noble metal selected from gold, platinum, palladium, titanium, molybdenum, tungsten, chromium, or an alloy mainly comprising at least one or more of these metals, or a layer of a conductive material of the ITO type, which has the advantage of also functioning as a diffusion barrier.

[0079] In this example, a 316L type stainless steel sheet with a thickness of 10 microns is used.

[0080] Deposition of a dense electrode layer by dip coating In principle, this electrode layer may be deposited either on the metal surface of the current collector, or on another dense or porous inorganic layer, for example a dense electrolyte layer or a porous separator.

[0081] Regardless of the chemical nature of the nanoparticles used, it is possible to deposit bimodal nanoparticles by the dip coating method; obviously, other deposition techniques mentioned above may also be used.

[0082] For example, Li4Ti5O 12 to produce a dense ceramic deposit, an ink composed of nanoparticles of two different sizes may be produced. Li4Ti5O 12 In the case of an anode consisting of, Li4Ti5O of about 5 nm 12The nanoparticles are synthesized by glycothermal methods (article "Impact of the Synthesis Parameters on the microstructure of nano-structured LTO prepared by glycothermal routes and 7 See “Li NMR structural investigations”, M. Odziomek, F. Chaput et al., J Sol-Gel Sci Technol 89, 225-233 (published 2019). In this synthesis, ligands are added to limit the aggregation of nanoparticles. These 5 nm diameter nanoparticles are obtained from 30 nm particle Li4Ti5O obtained by hydrothermal synthesis. 12 It is related to nanoparticles.

[0083] These nanoparticles are mixed with 70% by mass of 30 nm particles and 30% by mass of 5 nm nanoparticles in an ink containing 15% total dry extract in ethanol, with PVP as a stabilizer, and dispersed by ultrasound. Each dip coating pass produces only a layer of relatively limited thickness; the wet layer needs to be dried. To obtain a layer of the desired final thickness, the dip coating deposition and drying processes can be repeated as many times as necessary.

[0084] Although this series of dip coating / drying steps is time-consuming, the dip coating deposition method is simple, safe, easy to implement, easily industrializable, and allows for the acquisition of a homogeneous and compact final layer.

[0085] Treatment and characteristics of sedimentary layers As a general rule, the layer deposited by dip coating needs to be dried. After drying, heat treatment is performed in two stages. In the first stage, the deposit is maintained at 400°C for 10 minutes to calcine all organic compounds contained in the deposit. Next, the treatment temperature is raised to 550°C and maintained at this temperature for 1 hour to solidify the deposit.

[0086] The selection of nanoparticle materials clearly depends on the function of the layer to be deposited on the electrochemical, electrical, or electronic device in question. In principle, the nanoparticles used in this invention are inorganic and nonmetallic, and are known to be organically functionalized layers ("core-shell" type particles); this will be discussed later. These particles coated with organic layers are included here in the term "inorganic particles."

[0087] When the layer according to the present invention functions as the cathode of a battery, particularly a lithium-ion battery, it can be manufactured from, for example, a material P which is a cathode material selected from the following: -Oxide LiMn2O4, Li 1+x Mn 2-x O4(0 <x<0.15)、LiCoO2、LiNiO2、LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Ni 0.5-x X x O4(X is selected from Al, Fe, Cr, Co, Rh, Nd and other rare earth elements such as Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, 0 <x<0.1)、LiMn 2-x M x O4(M=Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or mixtures of these compounds, 0 <x<0.4)、LiFeO2、LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2, LiLiLi 0.8 Co 0.15 Al 0.05 O2, Lial x Mn 2-x O4 (0 ≤ x < 0.15), LiNi 1 / x Co 1 / y Mn 1 / z O2(x+y+z=10); - Phosphates LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3; phosphates of formula LiMM'PO4 (where M and M' (M≠M') are selected from Fe, Mn, Ni, Co, and V); -All lithium forms of the following chalcogenides: V2O5, V3O8, TiS2, titanium oxysulfide (TiO y S z (z=2-y and 0.3≦y≦1), tungsten oxysulfide (WO y S z (0.6<y<3 and 0.1<z<2)), CuS, CuS2, preferably Li x V2O5(0<x≦2), LixV3O8(0<x≦1.7), Li x TiS2(0<x≦1), titanium oxysulfide and lithium oxysulfide Li x TiO y S z (z=2-y, 0.3≦y≦1), Li x WO y S z , Li x CuS, Li x CuS2.

[0088] When the layer according to the present invention functions as an anode of a battery, particularly a lithium-ion battery, it can be manufactured from material P, which is an anode material selected from, for example, the following: -Carbon nanotubes, graphene, graphite; -Lithium iron phosphate (general formula LiFePO4); -A mixture of silicon and tin oxynitride (general formula Si a Sn b O y N z (a>0, b>0, a+b≦2, 0<y≦4, 0<z≦3))(also known as SiTON), in particular SiSn 0.87 O 1.2 N 1.72 ; likewise the oxynitride-carbide of general formula Si a Sn b C c O y N z (a>0, b>0, a+b≦2, 0<c<10, 0<y<24, 0<z<17); -Nitride Si x N y (in particular x=3 and y=4), Sn x N y (in particular x=3 and y=4), Znx N y (especially x=3 and y=2), Li 3-x M x N(0≦x≦0.5 when M=Co, 0≦x≦0.6 when M=Ni, 0≦x≦0.3 when M=Cu); Si 3-x M x N4(M=Co or Fe and 0≦x≦3), -oxides SnO2, SnO, Li2SnO3, SnSiO3, Li x SiO y (x≥0 and 2>y>0), Li4Ti5O 12 , TiNb2O7, Co3O4, SnB 0.6 P 0.4 O 2.9 and TiO2, -composite oxide TiNb2O7 containing 0 to 10 mass% of carbon, preferably the carbon is selected from graphene and carbon nanotubes, -general formula Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z (M 1 and M 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs and Sn, M 1 and M 2 are optionally the same as or different from each other, M 3 is at least one halogen, 0≦w≦5, 0≦x<1, 0≦y<2 and 0<z≦0.3).

[0089] When the layer according to the present invention functions as an electrolyte in a battery, particularly a lithium-ion battery, it may be produced from material P, which is an electrolyte material selected from, for example, the following: -general formula Li d A 1 x A 2y (TO4) z garnet(A 1 represents a cation with an oxidation state of +II, preferably Ca, Mg, Sr, Ba, Fe, Mn, Zn, Y, Gd, A 2 represents a cation with an oxidation state of +III, preferably Al, Fe, Cr, Ga, Ti, La, (TO4) represents an anion, T represents an atom with an oxidation state of +IV located at the center of a tetrahedron formed by oxygen atoms, TO4 advantageously represents a silicate or zirconate anion, and the element T with an oxidation state of +IV may be wholly or partially replaced by atoms with an oxidation state of +III or +V such as Al, Fe, As, V, Nb, In, Ta; d is 2 to 10, preferably 3 to 9, more preferably 4 to 8; x is 2.6 to 3.4 (preferably 2.8 to 3.2); y is 1.7 to 2.3 (preferably 1.9 to 2.1); z is 2.9 to 3.1; - garnet, preferably selected from the following: Li7La3Zr2O 12 ; Li6La2BaTa2O 12 ; Li 5.5 La3Nb 1.75 In 0.25 O 12 ; Li5La3M2O 12 (M=Nb or Ta or a mixture of these two compounds); Li 7-x Ba x La 3-x M2O 12 (0≦x≦1 and M=Nb or Ta or a mixture of these two compounds); Li 7-x La3Zr 2-x M x O 12 (0≦x≦2 and M=Al, Ga, Ta or a mixture of two or three of these compounds); - lithium phosphate, preferably selected from the following: NaSICON-type lithium phosphate, Li3PO4; LiPO3; Li3Al represented by "LASP" 0.4 Sc 1.6 (PO4)3; Li 1.2 Zr 1.9 Ca 0.1 (PO4)3; LiZr2(PO4)3; Li 1+3x Zr2(P1-x Si x O4)3(1.8 <x<2.3);Li 1+6x Zr2(P 1-x B x O4)3(0≦x≦0.25);Li3(Sc 2-x M x )(PO4)3(M=Al or Y and 0≦x≦1);Li 1+x M x (Sc) 2-x (PO4)3 (M = Al, Y, Ga or a mixture of the three compounds and 0 ≤ x ≤ 0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3 (0≦x≦0.8; 0≦y≦1 and M=Al or Y or a mixture of these two compounds); Li 1+x M x (Ga) 2-x (PO4)3 (M = Al, Y, or a mixture of these two compounds, and 0 ≤ x ≤ 0.8); Li represented as "LATP" 1+x Al x Ti 2-x (PO4)3(0≦x≦1); or Li represented by "LAGP" 1+x Al x Ge 2-x (PO4)3(0≦x≦1); or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 (0≦x≦0.8 and 0≦y≦1.0 and 0≦z≦0.6 and M=Al, Ga, or Y or a mixture of two or three of these compounds); Li 3+y (Sc 2-x M x )Q y P 3-y O 12 (M=Al and / or Y and Q=Si and / or Se, 0≦x≦0.8 and 0≦y≦1); or Li 1+x+y M x Sc 2-x Q y P 3-y O 12(M = Al, Y, Ga or a mixture of these three compounds, Q = Si and / or Se, 0 ≤ x ≤ 0.8 and 0 ≤ y ≤ 1); or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 (0≦x≦0.8, 0≦y≦1, 0≦z≦0.6, M=Al or Y or a mixture of these two compounds, Q=Si and / or Se); or Li 1+x Zr 2-x B x (PO4)3(0≦x≦0.25); or Li 1+x Zr 2-x Ca x (PO4)3(0≦x≦0.25); or Li 1+x M 3 x M 2-x P3O 12 (0≦x≦1 and M) 3 =Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si or mixtures of these compounds); Li 1+2x Ca x Zr 2-x (PO4)3(0≦x≦0.25); - Lithium borate, preferably selected from the following: Li3(Sc 2-x M x )(BO3)3(M=Al or Y and 0≦x≦1);Li 1+x M x (Sc) 2-x (BO3)3(M = Al, Y, Ga, or a mixture of these three compounds, and 0 ≤ x ≤ 0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3(0≦x≦0.8, 0≦y≦1 and M=Al or Y);Li 1+x M x (Ga) 2-x(BO3)3 (M is Al, Y, or a mixture of compounds of both, 0≦x≦0.8); Li3BO3, Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4; -oxynitrides, preferably Li3PO 4-x N 2x / 3 , Li4SiO 4-x N 2x / 3 , Li4GeO 4-x N 2x / 3 (0<x<4) or Li3BO 3-x N 2x / 3 (0<x<3); -Li x PO y N z a lithium compound called "LiPON", based on lithium oxynitride and phosphorus, represented by (x~2.8, 2y+3z~7.8, 0.16≦z≦0.4), in particular Li 2.9 PO 3.3 N 0.46 , compound Li w PO x N y S z (2x+3y+2z=5=w) or compound Li w PO x N y S z (3.2≦x≦3.8, 0.13≦y≦0.4, 0≦z≦0.2, 2.9≦w≦3.3), or Li t P x Al y O u N v S w compound of the form (5x+3y=5, 2u+3v+2w=5+t, 2.9≦t≦3.3, 0.84≦x≦0.94, 0.094≦y≦0.26, 3.2≦u≦3.8, 0.13≦v≦0.46, 0≦w≦0.2); -materials based on lithium phosphorus or boron oxynitride, called "LiPON" and "LIBON" respectively, which may comprise silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur and / or silicon, and in the case of materials based on lithium phosphorus oxynitride, boron; - A lithiated compound based on lithium, phosphorus and silicon oxynitride, called "LiSiPON", in particular Li 1.9 Si 0.28 P 1.0 O 1.1 N 1.0 ; - Lithium oxynitrides of the LiBON, LiBSO, LiSiPON, LiSON, thio-LiSiCON, LiPONB type (where B, P and S represent boron, phosphorus and sulfur respectively); -(1-x)LiBO 2-x Li2SO4 (0.4≦x≦0.8), which is a lithium oxynitride of the LiBSO type; - Lithium oxynitrides, preferably selected from the following: Li7La3Zr2O 12 or Li 5+x La3(Zr x , A 2-x )O 12 (A=Sc, Y, Al, Ga and 1.4≦x≦2), Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3 (0≦x≦0.16) (LLTO); - Silicates, preferably selected from Li2Si2O5, Li2SiO3, Li2Si2O6, LiAlSiO4, Li4SiO4, LiAlSi2O6; - Anti-perovskite type solid electrolytes selected from the following: Li3OA (A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I or a mixture of 2, 3 or 4 of these elements); Li (3-x) M x / 2 OA (0<x≦3, M is a divalent metal, preferably at least one element selected from Mg, Ca, Ba, Sr or a mixture of 2, 3 or 4 of these elements, A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I or a mixture of 2, 3 or 4 of these elements); Li (3-x) M 3 x / 3 OA (0≦x≦3, M 3A is a trivalent metal, A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I or a mixture of two, three, or four of these elements); or LiCOX z Y (1-z) (X and Y are the halogen atoms described above with respect to A, and 0 ≤ z ≤ 1); -Compound La 0.51 Li 0.34 Ti 2.94 Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4; -Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4, Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1+x Al x M 2-x (PO4)3(M=Ge, Ti and / or Hf and 0 <x<1)、Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 A formulation based on (0≦x≦1 and 0≦y≦1).

[0090] Use of coated nanoparticles ("core-shell" type) In principle, the nanoparticles used in the inks that help create these deposits for electrodes may also have a core-shell structure. Indeed, the performance of dense electrodes obtained by the method according to the present invention depends on their ionic and electronic conductivity. Furthermore, it may be important to apply a "shell" of organic or inorganic material with good electronic and / or ionic conductivity to the surface of the active material nanoparticles.

[0091] Therefore, in advantageous embodiments, the core is formed of an electrode material (anode or cathode), and the shell is formed of a material that is electrically conductive and does not hinder the passage of lithium ions. For example, the shell may be formed of a metal layer thin enough to allow lithium ions to pass through, or a graphite layer thin enough to allow lithium ions to pass through, or an inorganic or organic layer of an ion conductor that is also a good electronic conductor.

[0092] The core-shell approach can also be applied to the production of electrolytes. In a further embodiment, the core of the nanoparticles used in the method according to the present invention is formed of an electrolyte material, and the shell is formed of an inorganic or organic material which must be a good ion conductor, particularly lithium ions, and a good electronic insulator.

[0093] If the shell layer is an organic layer, it is preferable that this layer be made of a polymer material. Polymer layers have the advantage of being malleable, among other things, which facilitates the compression of the deposited layer using these particles.

[0094] Here, a method for preparing inorganic nanoparticles having a polymer shell is described. This is particularly suitable for nanoparticles of electrolyte materials, where the shell must be both an electrical insulator and an ionic conductor. This method, referred to herein as "functionalization" of inorganic nanoparticles to form a core with a shell, consists of grafting a molecule having a QZ-type structure onto the surface of the nanoparticle, where Q is a functional group that binds the molecule to the surface, and Z is preferably a PEO group.

[0095] As the Q group, complexing functional groups of surface cations of nanoparticles, such as phosphoric acid or phosphonate functional groups, can be used.

[0096] Preferably, the inorganic nanoparticles are functionalized with the following types of PEO derivatives: [ka] Here, X represents an alkyl chain or a hydrogen atom, n is 40 to 10,000 (preferably 50 to 200), m is 0 to 10, Q' is an embodiment of Q and is selected from the following group:

Chemical Formula

[0097] More preferably, the inorganic nanoparticles are functionalized with methoxy-PEO-phosphate,

Chemical Formula

[0098] According to an advantageous embodiment, the solution of Q-Z (or Q'-Z where applicable) is added to the colloidal suspension of electrolyte nanoparticles of the electrolyte or electronic insulator, so that the molar ratio between Q (including Q' herein) and all cations in the inorganic nanoparticles (abbreviated as "NP-C" herein) is 1 to 0.01, preferably 0.1 to 0.02. When the molar ratio Q / NP-C exceeds 1, the functionalization of electronic inorganic nanoparticles by the molecule Q-Z tends to induce a steric size such that the nanoparticles cannot be fully functionalized; this also depends on the size of the nanoparticles. When the molar ratio Q / NP-C is less than 0.01, the molecule Q-Z tends not to be in a sufficient amount to provide sufficient lithium ion conductivity; this also depends on the particle size. Using a large amount of Q-Z during functionalization leads to unnecessary consumption of Q-Z.

[0099] To perform functionalization of inorganic nanoparticles, a colloidal suspension of inorganic nanoparticles at a mass concentration of 0.1% to 50%, preferably 5% to 25%, more preferably 10% is used. At high concentrations, there may be a risk of crosslinking and lack of access to the surfaces to be functionalized (there is a risk of precipitation of particles that are not functionalized or are insufficiently functionalized). Preferably, the inorganic nanoparticles are dispersed in a liquid phase such as water or ethanol.

[0100] This reaction can be carried out in any suitable solvent that allows solubilization of molecule Q-Z.

[0101] According to molecule Q-Z, the functionalization conditions can be optimized by adjusting the reaction temperature, reaction time and the solvent used. After adding the solution of Q-Z to the colloidal suspension of electrolyte nanoparticles, the reaction medium is kept under stirring for 0 hours to 24 hours (preferably 5 minutes to 12 hours, more preferably 0.5 hours to 2 hours), so that at least part, preferably all of molecule Q-Z can be grafted onto the surface of the inorganic nanoparticles. The functionalization can preferably be carried out by heating at a temperature of 20°C to 100°C. The temperature of the reaction medium needs to be adapted to the selection of the functionalization molecule Q-Z.

[0102] Accordingly, these functionalized nanoparticles have a core or inorganic material and a shell of PEO. The thickness of the shell is usually 1 nm to 100 nm; this thickness can be measured by transmission electron microscopy after marking the polymer with ruthenium oxide (RuO4).

[0103] Advantageously, the nanoparticles thus functionalized are then purified by successive cycles of centrifugation and redispersion and / or by tangential flow filtration.

[0104] After redispersing the functionalized inorganic nanoparticles, the suspension can be reconcentrated by any appropriate means until the desired dry extract is obtained.

[0105] Advantageously, the dried extract of the suspension of PEO-functionalized inorganic nanoparticles contains more than 40% (by volume) of solid electrolyte material, preferably more than 60%, and more preferably more than 70%.

[0106] Densification of the layer formed by the organic core-shell type nanoparticles after deposition can be carried out by appropriate means, preferably by the following: a) Any mechanical means, in particular mechanical compression, preferably uniaxial compression; b) Thermocompression bonding, i.e., heat treatment under pressure. The optimal temperature depends closely on the chemical composition of the deposited material, as well as on the particle size and density of the layer. It is preferable to maintain a controlled atmosphere to prevent oxidation of the deposited particles and surface contamination.

[0107] Advantageously, solidification is carried out in a controlled atmosphere at a temperature between the ambient temperature and the melting temperature of the polymer used (usually PEO); thermocompression bonding can be carried out at ambient temperatures (about 20°C) to about 300°C; however, it is preferable not to exceed 200°C (or more preferably 100°C) to prevent degradation of the PEO.

[0108] As mentioned above, one of the advantages of organic shells is their malleability; PEO, for example, is a polymer that is easily deformable at relatively low pressures. Therefore, densification of nanoparticles of electrolytes or electronic insulators functionalized with polymers such as PEO can only be achieved by mechanical compression (the action of mechanical pressure). Advantageously, the compression is carried out at a pressure of 10 MPa to 500 MPa, preferably 50 MPa to 200 MPa, at a temperature of about 20°C to 200°C.

[0109] At the interface, PEO is amorphous, ensuring good ionic contact between solid electrolyte particles. Therefore, PEO can conduct lithium ions even without a liquid electrolyte; PEO is also an electronic insulator at the same time. This makes it suitable for assembling lithium-ion batteries at low temperatures, as it limits the risk of interdiffusion at the interface between the electrolyte and electrodes.

[0110] In lithium-ion batteries, the thickness of the electrolyte layer obtained after densification is less than 10 μm, preferably less than 6 μm, and preferably less than 5 μm, thereby limiting the thickness and weight of the battery without impairing its characteristics.

[0111] Use of the method according to the present invention for depositing layers on a device containing a mesoporous layer The method according to the present invention enables the deposition of inorganic dense layers in electrochemical and other devices such as lithium-ion batteries. In these devices, the dense layer may function as an anode, cathode, or electrode, and the device may contain several inorganic dense layers according to the present invention. These devices may be of the "all-solid" type, and the dense layer has only very low porosity. According to a variation of the present invention, the device also contains at least one porous inorganic layer.

[0112] According to this modification of the present invention, the “porous inorganic layer” is preferably mesoporous and may be deposited using a method selected from the group formed by: electrophoresis, inkjet printing and flexographic printing; and a coating method selected from roll coating, curtain coating, doctor blade coating, slot die coating and dip coating; and the use of a suspension of nanoparticle aggregates or clumps, preferably a concentrated suspension containing nanoparticle clumps.

[0113] More specifically, the average primary diameter D 50 A colloidal suspension is used that contains aggregates or clumps of nanoparticles of at least one inorganic material, with an average diameter of 2 nm to 100 nm, preferably 2 nm to 60 nm, wherein the aggregates or clumps typically have an average diameter of D 50 The nanoparticles have a size of 50 nm to 300 nm (preferably 100 nm to 200 nm). Next, the layer thus obtained is dried and compacted by pressurization and / or heating to obtain a preferably mesoporous inorganic porous layer. This method is particularly advantageous for nanoparticles formed from electrolyte materials.

[0114] The mesoporous layer may be deposited on a dense layer deposited by the method according to the present invention, or the dense layer may be deposited on the mesoporous layer prepared by the method described above.

[0115] The porous layer must be impregnated with a mobile cation carrier liquid so that it can perform its electrolyte function; in the case of a lithium-ion battery, this cation is a lithium cation. This lithium-ion carrier phase is preferably selected from the group formed by: • An electrolyte consisting of at least one aprotic solvent and at least one lithium salt; • An electrolyte composed of at least one ionic liquid or ionic polyliquid and at least one lithium salt; A mixture of at least one aprotic solvent, at least one ionic liquid or ionic polyliquid, and at least one lithium salt; • Polymers made ionically conductive by adding at least one lithium salt; and A polymer made ion-conductive by adding a liquid electrolyte in either a polymer phase or a mesoporous structure. The polymer is preferably selected from the group formed by poly(ethylene oxide), poly(propylene oxide), polydimethylsiloxane, polyacrylonitrile, poly(methyl methacrylate), poly(vinyl chloride), poly(vinylidene fluoride), and PVDF-hexafluoropropylene.

[0116] Manufacturing examples of lithium-ion microbatteries This section describes a method for manufacturing a lithium-ion microbattery using the layer according to the present invention.

[0117] a) Preparation of electrodes by the deposition method according to the present invention The first dense Li4Ti5O obtained by the method described in the section "Deposition of a dense electrode layer by dip coating" 12 The electrodes were deposited. A second, denser LiMn2O4 electrode was deposited using the same method.

[0118] Next, a mesoporous thin film of Li₃PO₄ mass, prepared as described later and functioning as a battery separator, was deposited on each of these two electrodes.

[0119] b) Deposition of Separation Layer A suspension of Li₃PO₄ nanoparticles was prepared using the two solutions described below: First, 45.76 g of CH₃COOLi·2H₂O was dissolved in 448 ml of water, then 224 ml of ethanol was added to this medium under vigorous stirring to obtain Solution A. Next, 16.24 g of H₃PO₄ (85 wt% in water) was diluted with 422.4 ml of water, and 182.4 ml of ethanol was added to this solution to obtain a second solution, hereinafter referred to as Solution B. Solution B was then added to Solution A under vigorous stirring.

[0120] After the foam formed during mixing disappeared and the resulting solution became completely transparent, it was added to 4.8 liters of acetone under the operation of an Ultra-Turrax type homogenizer to homogenize the medium. A white precipitate suspended in the liquid phase was immediately observed.

[0121] After homogenizing the reaction medium for 5 minutes, it was maintained under magnetic stirring for 10 minutes. The whole was left to stand for 1 to 2 hours. The supernatant was removed, and the remaining suspension was centrifuged at 6000 g for 10 minutes. Next, 1.2 liters of water was added to resuspend the precipitate (using sonotrode and magnetic stirring). This type of washing was then performed two more times with ethanol. 15 ml of a solution of bis[2-(methacryloyloxy)ethyl] phosphate was added at 1 g / ml to the colloidal suspension in ethanol thus obtained under vigorous stirring. In this way, the suspension was further stabilized. The suspension was then ultrasonicated using a sonotrode. Next, the suspension was centrifuged at 6000 g for 10 minutes. The pellet was then redispersed in 1.2 liters of ethanol, followed by centrifugation at 6000 g for 10 minutes. The pellet thus obtained is redispersed in 900 ml of ethanol to obtain a 15 g / l suspension that can be subjected to electrophoretic deposition.

[0122] In this way, a mass of approximately 200 nm consisting of 10 nm primary particles of Li3PO4 was obtained by suspending it in ethanol.

[0123] A porous thin layer of Li3PO4 was deposited by electrophoresis onto the surfaces of the previously prepared anode and cathode by applying a 20 V / cm electric field for 90 seconds to the Li3PO4 nanoparticle suspension obtained above, resulting in a layer of approximately 2 μm thickness. Next, this layer was air-dried at 120°C, and then calcined at 350°C for 120 minutes to remove any trace organic residues.

[0124] c) Assembly of electrodes and separators Pre-prepared electrodes (Li 1+x Mn 2-y O4 and Li4Ti5O 12 After depositing a 2 μm porous Li3PO4 film on each of the subsystems, the two subsystems were stacked so that the Li3PO4 films were in contact. Next, this stack was hot-pressed in a vacuum between two planar plates. To do this, first the stack was placed under a pressure of 5 MPa, and then 10 -3 The material was vacuum-dried in a bar for 30 minutes. Next, the press plate was heated to 550°C at a rate of 0.4°C / second. Then, the laminate was thermally compressed at 550°C under a pressure of 45 MPa for 20 minutes, and the system was cooled to ambient temperature. Finally, the assembly was dried in a vacuum (10 mbar) at 120°C for 48 hours.

[0125] d) Impregnation of the separator with a liquid electrolyte Next, the assembly was impregnated under an anhydrous atmosphere by immersion in an electrolyte solution containing PYR14TFSI and 0.7 M LiTFSI. PYR14TFSI is the standard abbreviation for 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide. LITFSI is the standard abbreviation for lithium bis-trifluoromethanesulfonimide (CAS number: 90076-65-6). This ionic liquid instantly enters the pores of the separator by capillary action. Both ends of the system were kept immersed in the electrolyte mixture for 5 minutes each.

[0126] It should be noted that in industrial manufacturing methods, impregnation is performed after the battery is sealed, and then the electrical contact components are manufactured.

[0127] In principle, the battery according to the present invention may be a lithium-ion microbattery. In particular, it can be designed and sized to have a capacitance of about 1 mAh or less (generally called a "microbattery"). Typically, microbatteries are designed to be compatible with manufacturing methods for microelectronics.

[0128] These microbatteries can be manufactured in the following ways: -The layer according to the present invention is of the "all-solid" type, that is, it does not contain an impregnated liquid phase or paste phase (the liquid phase or paste phase is a lithium ion conductive medium that can act as an electrolyte). -Or, an electrode and a mesoporous "all-solid" type separator according to the present invention, which is impregnated with a liquid phase or paste phase, typically a lithium-ion conductive medium, which spontaneously enters the inside of the layer and no longer leaves it, and which can be considered a quasi-solid. -or, an electrode and a porous separator impregnated with the present invention (i.e., a layer having a grid of open pores that can be impregnated with a liquid phase or paste phase and give these layers wettability).

[0129] Different embodiments of the present invention As is evident from the given description, the present invention has several modes, features, and combinations of features, which are summarized below.

[0130] A first aspect of the present invention is a method for producing a dense layer, comprising the following steps: - A step of supplying a suspension of non-aggregated nanoparticles of the substrate and inorganic material P; - A step of depositing a layer on the substrate using a suspension of primary nanoparticles of the material P; - A step of drying the obtained layer; - A step of densifying the dried layer by mechanical compression and / or heat treatment; It is understood that the third and fourth steps may be performed at least partially simultaneously or during the heating process; The above method comprises a suspension of non-aggregated nanoparticles of material P having a size distribution, wherein the size is D 50 The following method is characterized by being defined by the value of: The distribution consists of nanoparticles of material P with a first size D1 of 20 nm to 50 nm, and D which is at least 5 times smaller than the value of D1. 50 It includes nanoparticles of material P of a second size D2, characterized by a value.

[0131] According to the alternative, the distribution is such that the average size of nanoparticles in material P is less than 50 nm, and the ratio of the standard deviation to the average size is greater than 0.6.

[0132] According to this first modification of the first embodiment, the suspension of non-aggregated nanoparticles of material P comprises nanoparticles of material P with a first size D1 of 20 nm to 50 nm and D which is at least 5 times smaller than the value of D1. 50 The material comprises nanoparticles of a second size D2 material P characterized by a value, wherein the particles of size D1 account for 50-75% of the total mass of the nanoparticles. Preferably, the average diameter of the second group is at least 1 / 15, and preferably at least 1 / 12, of the average diameter of the first nanoparticle group.

[0133] According to a second modification that is also compatible with the first modification of this first embodiment, a suspension of unaggregated nanoparticles of material P is obtained using a monodisperse suspension of nanoparticles of size D1.

[0134] According to a third modification, which is also compatible with the first and second modifications of this first mode, a suspension of nanoparticles of size D2 is obtained using a monodisperse suspension.

[0135] According to a fourth modification that is also compatible with the first, second, and third modifications of this first embodiment, a mixture of two nanoparticle size groups is used such that the average diameter of the maximum distribution does not exceed 100 nm, preferably 50 nm. Preferably, the first group of the largest nanoparticles is σ / R mean It has a size distribution characterized by a ratio of less than 0.6.

[0136] In the first sub-modification of this modification, preferably, the largest nanoparticle population represents 50% to 75% of the dry extract of the sediment, and the second nanoparticle population represents 50% to 25% of the dry extract of the sediment (these percentages are expressed as mass % of the total mass of nanoparticles in the sediment).

[0137] In the second sub-modification of this fourth modification, the average diameter of the particles in this second group is at least 5 times smaller than the average diameter of the particles in the first nanoparticle group, preferably the average diameter of the second group is at least 1 / 15 of that of the first nanoparticle group, preferably at least 1 / 12. Preferably, this second group is σ / R mean It has a size distribution characterized by a ratio of less than 0.6.

[0138] According to a fifth modification, which is also compatible with the first, second, third, and fourth modifications of the first embodiment, for the deposition of the dense layer, printing techniques, particularly inkjet and flexographic printing, electrophoretic techniques, and coating techniques, particularly roll coating, curtain coating, doctor blade coating, dip coating, or slot die coating, are used.

[0139] According to the sixth modification, which is also compatible with the first, second, third, fourth, and fifth modifications of this first form, the suspension has a viscosity of 20 cP to 2000 cP as measured at 20°C.

[0140] According to the seventh modification, which is also compatible with the first, second, third, fourth, fifth, and sixth modifications of this first embodiment, the material P is an inorganic material, preferably selected from the group formed by: - Preferably, a cathode material selected from the group formed by: - Oxides LiMn2O4, Li 1+x Mn 2-x O4(0<x<0.15), LiCoO2, LiNiO2, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Ni 0.5-x X x O4(X is selected from Al, Fe, Cr, Co, Rh, Nd and other rare earths such as Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, 0<x<0.1), LiMn 2-x M x O4(M=Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or a mixture of these compounds, 0<x<0.4), LiFeO2, LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiAl x Mn 2-x O4(0≦x<0.15), LiNi 1 / x Co 1 / y Mn 1 / z O2(x+y+z=10); - Phosphates LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3; phosphates of formula LiMM'PO4 (M and M' (M≠M') are selected from Fe, Mn, Ni, Co, V); - All lithium forms of the following chalcogenides: V2O5, V3O8, TiS2, titanium oxysulfide (TiO y S z (z=2-y and 0.3≦y≦1), tungsten oxysulfide (WO y S z (0.6<y<3 and 0.1<z<2)), CuS, CuS2, preferably Li x V2O5(0<x≦2), LixV3O8(0<x≦1.7), Li x TiS2(0<x≦1), titanium oxysulfide and lithium oxysulfide Lix TiO y S z (z=2-y, 0.3≦y≦1), Li x WO y S z , Li x CuS, Li x CuS2; - preferably, an anode material selected from the group formed by: - carbon nanotubes, graphene, graphite; - lithium iron phosphate (general formula LiFePO4); - a mixture of silicon and tin oxynitride (general formula Si a Sn b O y N z (a>0, b>0, a+b≦2, 0<y≦4, 0<z≦3))(also known as SiTON), in particular SiSn 0.87 O 1.2 N 1.72 ; likewise the oxynitride-carbide of general formula Si a Sn b C c O y N z (a>0, b>0, a+b≦2, 0<c<10, 0<y<24, 0<z<17); - nitride Si x N y (in particular x=3 and y=4), Sn x N y (in particular x=3 and y=4), Zn x N y (in particular x=3 and y=2), Li 3-x M x N(0≦x≦0.5 when M=Co, 0≦x≦0.6 when M=Ni, 0≦x≦0.3 when M=Cu); Si 3-x M x N4(M=Co or Fe and 0≦x≦3), - oxides SnO2, SnO, Li2SnO3, SnSiO3, Li x SiO y (x>=0 and 2>y>0), Li4Ti5O 12 , TiNb2O7, Co3O4, SnB 0.6 P 0.4 O2.9 and TiO2, - A composite oxide TiNb2O7 containing 0-10% by mass of carbon, preferably in which the carbon is selected from graphene and carbon nanotubes; - Preferably, an electrolyte material selected from the group formed by the following: -General formula Li d A 1 x A 2 y (TO4) z Garnet (A 1 represents a cation with oxidation degree +II, preferably Ca, Mg, Sr, Ba, Fe, Mn, Zn, Y, Gd, and A 2 (TO4) represents a cation with oxidation degree +III, preferably Al, Fe, Cr, Ga, Ti, or La; (TO4) represents an anion, T is an atom with oxidation degree +IV located at the center of a tetrahedron formed by oxygen atoms; TO4 preferably represents an anion of silicate or zirconate; the element T with oxidation degree +IV may be replaced in whole or in part with an atom with oxidation degree +III or +V such as Al, Fe, As, V, Nb, In, or Ta; d is 2 to 10, preferably 3 to 9, more preferably 4 to 8; x is 2.6 to 3.4 (preferably 2.8 to 3.2); y is 1.7 to 2.3 (preferably 1.9 to 2.1); z is 2.9 to 3.1. - Garnet, preferably selected from the following: Li7La3Zr2O 12 ;Li6La2BaTa2O 12 ;Li 5.5 La3Nb 1.75 In 0.25 O 12 Li5La3M2O 12 (M=Nb or Ta or a mixture of these two compounds); Li 7-x Ba x La 3-x M2O 12 (0 ≤ x ≤ 1 and M = Nb or Ta or a mixture of these two compounds); Li 7-x La3Zr 2-x M x O 12(0 ≤ x ≤ 2 and M = Al, Ga, Ta, or a mixture of two or three of these compounds); - Lithium phosphate, preferably selected from the following: NaSICON type lithium phosphate, Li3PO4; LiPO3; Li3Al represented as "LASP". 0.4 Sc 1.6 (PO4)3;Li 1.2 Zr 1.9 Ca 0.1 (PO4)3;LiZr2(PO4)3;Li 1+3x Zr2(P 1-x Si x O4)3(1.8 <x<2.3);Li 1+6x Zr2(P 1-x B x O4)3(0≦x≦0.25);Li3(Sc 2-x M x )(PO4)3(M=Al or Y and 0≦x≦1);Li 1+x M x (Sc) 2-x (PO4)3 (M = Al, Y, Ga or a mixture of the three compounds and 0 ≤ x ≤ 0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (PO4)3 (0≦x≦0.8; 0≦y≦1 and M=Al or Y or a mixture of these two compounds); Li 1+x M x (Ga) 2-x (PO4)3 (M = Al, Y, or a mixture of these two compounds, and 0 ≤ x ≤ 0.8); Li represented as "LATP" 1+x Al x Ti 2-x (PO4)3(0≦x≦1); or Li represented by "LAGP" 1+x Al x Ge 2-x (PO4)3(0≦x≦1); or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12(0≦x≦0.8 and 0≦y≦1.0 and 0≦z≦0.6 and M=Al, Ga, or Y or a mixture of two or three of these compounds); Li 3+y (Sc 2-x M x )Q y P 3-y O 12 (M=Al and / or Y and Q=Si and / or Se, 0≦x≦0.8 and 0≦y≦1); or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 (M = Al, Y, Ga or a mixture of these three compounds, Q = Si and / or Se, 0 ≤ x ≤ 0.8 and 0 ≤ y ≤ 1); or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 (0≦x≦0.8, 0≦y≦1, 0≦z≦0.6, M=Al or Y or a mixture of these two compounds, Q=Si and / or Se); or Li 1+x Zr 2-x B x (PO4)3(0≦x≦0.25); or Li 1+x Zr 2-x Ca x (PO4)3(0≦x≦0.25); or Li 1+x M 3 x M 2-x P3O 12 (0≦x≦1 and M) 3 =Cr, V, Ca, B, Mg, Bi and / or Mo, M=Sc, Sn, Zr, Hf, Se or Si or mixtures of these compounds); Li 1+2x Ca x Zr 2-x (PO4)3(0≦x≦0.25); - Lithium borate, preferably selected from the following: Li3(Sc 2-x M x )(BO3)3(M=Al or Y and 0≦x≦1);Li 1+x M x (Sc) 2-x(BO3)3 (where M is Al, Y, Ga or a mixture of these three compounds, and 0≦x≦0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (BO3)3 (0≦x≦0.8, 0≦y≦1 and M=Al or Y); Li 1+x M x (Ga) 2-x (BO3)3 (where M is Al, Y, or a mixture of both compounds, 0≦x≦0.8); Li3BO3, Li3BO3-Li2SO4, Li3BO3-Li2SiO4, Li3BO3-Li2SiO4-Li2SO4; -oxynitrides, preferably Li3PO 4-x N 2x / 3 , Li4SiO 4-x N 2x / 3 , Li4GeO 4-x N 2x / 3 (0<x<4) or Li3BO 3-x N 2x / 3 (0<x<3); -Li x PO y N z lithium compound called "LiPON", based on lithium oxynitride and phosphorus represented by (x~2.8 and 2y+3z~7.8 and 0.16≦z≦0.4), in particular Li 2.9 PO 3.3 N 0.46 , compound Li w PO x N y S z (2x+3y+2z=5=w) or compound Li w PO x N y S z (3.2≦x≦3.8, 0.13≦y≦0.4, 0≦z≦0.2, 2.9≦w≦3.3), or Li t P x Al y O u N v S wCompounds of the form (5x+3y=5, 2u+3v+2w=5+t, 2.9≦t≦3.3, 0.84≦x≦0.94, 0.094≦y≦0.26, 3.2≦u≦3.8, 0.13≦v≦0.46, 0≦w≦0.2); - Materials based on lithium phosphorus or boronitride, referred to as "LiPON" and "LIBON," respectively, which may contain silicon, sulfur, zirconium, aluminum, or a combination of aluminum, boron, sulfur, and / or silicon, and, in the case of materials based on lithium phosphate nitride, boron; - Lithium compounds based on lithium, phosphorus, and silicon oxynitride, called "LiSiPON," especially Li 1.9 Si 0.28 P 1.0 O 1.1 N 1.0 ; -Lithium oxynitrides of the LiBON, LiBSO, LiSiPON, LiSON, thio-LiSiCON, and LiPONB types (B, P, and S represent boron, phosphorus, and sulfur, respectively); -(1-x)LiBO 2-x Li2SO4 (0.4 ≤ x ≤ 0.8) is a LiBSO-type lithium oxynitride; - Lithium oxynitride, preferably selected from: Li7La3Zr2O 12 or Li 5+x La3(Zr x , A 2-x )O 12 (A=Sc, Y, Al, Ga and 1.4≦x≦2), Li 0.35 La 0.55 TiO3 or Li 3x La 2 / 3-x TiO3(0≦x≦0.16)(LLTO); - Silicates, preferably selected from Li2Si2O5, Li2SiO3, Li2Si2O6, LiAlSiO4, Li4SiO4, and LiAlSi2O6; -anti-perovskite type solid electrolyte selected from the following: Li3OA (A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I, or a mixture of 2, 3 or 4 of these elements); Li (3-x) M x / 2 OA (0<x≦3, M is a divalent metal, preferably at least one element selected from Mg, Ca, Ba, Sr, or a mixture of 2, 3 or 4 of these elements, A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I, or a mixture of 2, 3 or 4 of these elements); Li (3-x) M 3 x / 3 OA (0≦x≦3, M 3 is a trivalent metal, A is a halogen atom or a mixture of halogen atoms, preferably at least one element selected from F, Cl, Br, I, or a mixture of 2, 3 or 4 of these elements); or LiCOX z Y (1-z) (X and Y are the halogen atoms defined above for A, and 0≦z≦1); -Compound La 0.51 Li 0.34 Ti 2.94 , Li 3.4 V 0.4 Ge 0.6 O4, Li2O-Nb2O5, LiAlGaSPO4; -Li2CO3, B2O3, Li2O, Al(PO3)3LiF, P2S3, Li2S, Li3N, Li 14 Zn(GeO4)4, Li 3.6 Ge 0.6 V 0.4 O4, LiTi2(PO4)3, Li 3.25 Ge 0.25 P 0.25 S4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1+x Al x M 2-x (PO4)3 (M=Ge, Ti and / or Hf, and 0<x<1), Li 1+x+y Al x Ti2-x Si y P 3-y O 12 A formulation based on (0≦x≦1 and 0≦y≦1).

[0141] According to the eighth modification, which is also compatible with the first, second, third, fourth, fifth, sixth, and seventh modifications of this first embodiment, the nanoparticles of the inorganic material P include nanoparticles composed of a core and a shell, wherein the core is formed of the inorganic material P and the shell is formed of another material, preferably an organic material, and more preferably a polymeric material.

[0142] In the first sub-modification of this eighth modification, the shell is formed from a material that is an electron conductor.

[0143] In the second sub-modification of this eighth modification, the shell is formed from a material that is an electronic insulator and a cation conductor, particularly a lithium ion conductor.

[0144] In the third sub-modification of this eighth modification, the shell is formed from a material that is an electron conductor and a cation conductor, particularly a lithium ion conductor.

[0145] According to the ninth modification, which is also compatible with the first, second, third, fourth, fifth, sixth, seventh, and eighth modifications of this first embodiment, the nanoparticles of the inorganic material P (or, in the case of the eighth modification, the core made of the inorganic material P of the nanoparticles) are prepared in a suspension by precipitation.

[0146] A second embodiment of the present invention is a method for manufacturing at least one dense layer in a lithium-ion battery, wherein the method for manufacturing the dense layer is according to the first embodiment of the present invention and has all the modifications and all the sub-modifications described in relation to the first embodiment.

[0147] According to the first modification of this second embodiment, the material P is selected such that the dense layer can function as the anode of a lithium-ion battery.

[0148] According to this second modification of the second embodiment, the material P is selected such that the dense layer can function as the cathode of a lithium-ion battery.

[0149] According to a third modification, which is also compatible with the first and second modifications of this second embodiment, the material P is selected such that the dense layer can function as an electrolyte for a lithium-ion battery.

[0150] A third aspect of the present invention is a method for producing at least one dense layer in a lithium-ion battery, wherein the dense layer can be obtained by the method of the first aspect of the present invention, in all the modifications and sub-modifications described in relation to the first aspect.

[0151] According to the first modification of this third embodiment, the material P is selected such that the dense layer can function as the anode of a lithium-ion battery.

[0152] According to a second modification that also fits the first modification of this third mode, the material P is selected such that the dense layer can function as the cathode of a lithium-ion battery.

[0153] According to the third modification, which is also compatible with the first and second modifications of this third embodiment, the material P is selected such that the dense layer can function as an electrolyte for a lithium-ion battery.

[0154] A fourth embodiment of the present invention is a method for manufacturing a lithium-ion battery, the battery comprising at least one dense electrode layer deposited in the manner of the first embodiment of the present invention, comprising all the modifications and all the sub-modifications described in relation to the first embodiment, and preferably also comprising a porous layer intended to form a separator, using an electrolyte material according to a seventh modification of the first embodiment of the present invention.

[0155] According to the first modified example of this fourth mode, the porous layer is a mesoporous layer, preferably with a mesoporous volume of 25% to 75%, more preferably 30% to 60%.

[0156] According to a second modification that also fits the first modification of this fourth aspect, the method for depositing the porous layer is preferably a method selected from the group formed by: electrophoresis, preferably a printing method selected from inkjet printing and flexographic printing, and preferably a coating method selected from roll coating, curtain coating, doctor blade coating, slot die coating and dip coating, in which case the deposition is carried out using a suspension of nanoparticle aggregates or lumps.

[0157] According to a third modification, which is also compatible with the first and second modifications of this fourth mode, a concentrated suspension containing nanoparticles is used to deposit the porous layer.

[0158] According to this fourth modification, which is also compatible with the first, second, and third modifications of this fourth form, the colloidal suspension has an average primary diameter D 50 This is used to deposit the porous layer which contains aggregates or clumps of nanoparticles of at least one inorganic material, which are 2 nm to 100 nm in size, preferably 2 nm to 60 nm, and the aggregates or clumps typically have an average diameter D of 50 nm to 300 nm, preferably 100 nm to 200 nm. 50 It has.

[0159] According to a fifth modification, which is also compatible with the first, second, third, and fourth modifications of this fourth mode, the obtained layer is dried and compacted by pressurization and / or heating to obtain a preferably mesoporous, inorganic porous layer.

[0160] According to the sixth modification, which is also compatible with the first, second, third, fourth, and fifth modifications of this fourth mode, the porous layer is deposited on the dense layer.

[0161] According to the seventh modification, which is also compatible with the first, second, third, fourth, fifth, and sixth modifications of this fourth mode, the dense layer is deposited on the mesoporous layer.

[0162] According to the eighth modification, which is also compatible with the first, second, third, fourth, fifth, sixth, and seventh modifications of this fourth mode, the second electrode layer is deposited on the porous layer.

[0163] According to the first sub-modification of this eighth modification, the second electrode layer is a dense electrode deposited by the method according to the first aspect of the present invention.

[0164] According to the second sub-modification of this eighth modification, the second electrode layer is a porous electrode, and preferably according to a method for preparing a porous separation layer related to the fourth aspect of the present invention, and particularly according to the first, second, third, fourth, and fifth modifications, the separator material is replaced with a suitable electrode material, and preferably according to the seventh modification of the first aspect of the present invention, it is prepared using an anode material or a cathode material.

[0165] According to the ninth modification, which is also compatible with the first, second, third, fourth, fifth, sixth, seventh, and eighth modifications of this fourth mode, the porous separation layer is impregnated with a mobile lithium ion carrier liquid, preferably selected from the group formed by: • An electrolyte consisting of at least one aprotic solvent and at least one lithium salt; • An electrolyte composed of at least one ionic liquid or ionic polyliquid and at least one lithium salt; A mixture of at least one aprotic solvent, at least one ionic liquid or ionic polyliquid, and at least one lithium salt; • Polymers made ionically conductive by adding at least one lithium salt; and A polymer made ion-conductive by adding a liquid electrolyte in either a polymer phase or a mesoporous structure. The polymer is preferably selected from the group formed by poly(ethylene oxide), poly(propylene oxide), polydimethylsiloxane, polyacrylonitrile, poly(methyl methacrylate), poly(vinyl chloride), poly(vinylidene fluoride), and PVDF-hexafluoropropylene.

[0166] A fifth aspect of the present invention is a dense layer obtained by the method of the first aspect of the present invention, having all the modifications and all the sub-modifications described in relation to the first aspect of the present invention.

[0167] According to the first modification of this fifth embodiment, the material P is selected such that the dense layer can function as the anode of a lithium-ion battery.

[0168] According to the second modification, which is also compatible with the first modification of this fifth mode, the material P is selected such that the dense layer can function as the cathode of a lithium-ion battery.

[0169] According to the third modification, which is also compatible with the first and second modifications of this fifth mode, the material P is selected such that the dense layer can function as an electrolyte for a lithium-ion battery.

[0170] According to the fourth modification, which is also compatible with the first, second, and third modifications of this fifth mode, the dense layer has a density of at least 90% of the theoretical density, preferably at least 95% of the theoretical density, more preferably at least 96% of the theoretical density, and optimally at least 97% of the theoretical density.

[0171] A sixth aspect of the present invention is a dense layer in a lithium-ion battery that can be obtained by the method according to the first aspect of the present invention, having all the modifications and all the sub-modifications described in relation to the first aspect of the present invention.

[0172] According to the first modification of this sixth form, the material P is selected such that the dense layer can function as the anode of a lithium-ion battery.

[0173] According to the second modification, which is also compatible with the first modification of this sixth mode, the material P is selected such that the dense layer can function as the cathode of a lithium-ion battery.

[0174] According to the third modification, which is also compatible with the first and second modifications of this sixth form, the material P is selected such that the dense layer can function as an electrolyte for a lithium-ion battery.

[0175] A seventh aspect of the present invention is a lithium-ion battery having a capacitance not exceeding 1 mAh, referred to herein as a "microbattery," comprising at least one dense layer according to the fifth aspect of the present invention, and including all the modifications and all the sub-modifications described in relation to the fifth aspect of the present invention.

[0176] According to this first modification of the seventh embodiment, the microbattery includes an anode which is a dense layer according to the fifth embodiment of the present invention.

[0177] According to this second modification of the seventh embodiment, the microbattery includes a cathode which is a dense layer according to the fifth embodiment of the present invention.

[0178] According to the third modification of this seventh embodiment, the microbattery comprises an anode and a cathode which are dense layers according to the fifth embodiment of the present invention.

[0179] According to the fourth modification of this seventh embodiment, the microbattery includes an anode, a cathode, and an electrolyte which are dense layers according to the fifth embodiment of the present invention.

[0180] According to the fourth modification, which is also compatible with the first, second, and third modifications of this seventh embodiment, the microbattery includes a separator which is a porous layer according to the fourth embodiment of the present invention.

Claims

1. A method for manufacturing a dense layer, (i) A step of supplying a suspension of non-aggregated nanoparticles of a metal substrate and an inorganic material P, (ii) A step of depositing a layer on the substrate using a suspension of non-aggregated nanoparticles of the material P, The steps include drying the obtained layer (iii), (iv) a step of densifying the dried layer by mechanical compression and / or heat treatment, Steps (iii) and (iv) may be performed at least partially simultaneously or during the temperature rise. The above method comprises a suspension of non-aggregated nanoparticles of material P having a size distribution, The aforementioned size distribution is characterized by the Dv50 value, and is as follows: The size distribution includes nanoparticles of material P of a first size D1 of 20 nm to 50 nm, and nanoparticles of material P of a second size D2 characterized by a Dv50 value that is at least five times smaller than the value of the first size D1, or The size distribution is such that the Dv50 value of the nanoparticles of the material P is less than 50 nm, and the ratio of the standard deviation to the Dv50 value is greater than 0.

6. The manufacturing method is characterized in that the material P is selected from the group formed by the following: -oxide LiMn 2 O 4 , Li 1+x Mn 2-x O 4 (0<x<0.15), LiCoO 2 , LiNiO 2 , LiMn 1.5 Ni 0.5 O 4 , LiMn 1.5 Ni 0.5-x X x O 4 (X is selected from Al, Fe, Cr, Co, Rh, Nd and other rare earth elements, 0<x<0.1), LiMn 2-x M x O 4 (M=Er, Dy, Gd, Tb, Yb, Al, Y, Ni, Co, Ti, Sn, As, Mg or a mixture of these compounds, 0<x<0.4), LiFeO 2 , LiMn 1/3 Ni 1/3 Co 1/3 O 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2 , LiAl x Mn 2-x O 4 (0≦x<0.15), LiNi 1/x Co 1/y Mn 1/z O 2 (x+y+z=10); - LiFePO phosphate 4 LiMnPO 4 LiCoPO 4 LiNiPO 4 Li 3 V 2 (PO 4 ) 3 ;Formula LiMM'PO 4 Phosphates of (M and M' (M≠M') are selected from Fe, Mn, Ni, Co, V); - All lithium forms of the following chalcogenides: V 2 O 5 , V 3 O 8 TiS 2 Titanium oxysulfide (TiO y S z (z = 2 - y and 0.3 ≤ y ≤ 1), tungsten oxysulfide (WO y S z (0.6 < y < 3 and 0.1 < z < 2), CuS, CuS 2 Li x V 2 O 5 (0<x≦2), LixV 3 O 8 (0<x≦1.7), Li x TiS 2 (0 < x ≤ 1), titanium oxysulfide and lithium oxysulfide Li x TiO y S z (z=2-y, 0.3≦y≦1), Li x WO y S z Li x CuS, Li x CuS 2 ; - Carbon nanotubes, graphene, graphite; - Formula LiFePO 4 Lithium iron phosphate, indicated by [this symbol]; - A mixture of silicon and tin nitride (general formula Si a Sn b O y N z (a > 0, b > 0, a + b ≤ 2, 0 < y ≤ 4, 0 < z ≤ 3) (also known as SiTON), similarly the general formula Si a Sn b C c O y N z Oxynitride-carbide (a>0, b>0, a+b≦2, 0<c<10, 0<y<24, 0<z<17); - Nitride Si x N y (x=3 and y=4), Sn x N y (x=3 and y=4), Zn x N y (x=3 and y=2), Li 3-x M x N (If M=Co, then 0≦x≦0.5; if M=Ni, then 0≦x≦0.6; if M=Cu, then 0≦x≦0.3); Si 3-x M x N 4 (M = Co or Fe and 0 ≤ x ≤ 3); -oxide SnO 2 , SnO, Li 2 SnO 3 , SnSiO 3 , Li x SiO y (x>=0 and 2>y>0), Li 4 Ti 5 O 12 , TiNb 2 O 7 , Co 3 O 4 , SnB 0.6 P 0.4 O 2.9 and TiO 2 ; - Composite oxide TiNb containing 0 to 10% by mass of carbon 2 O 7 ; - General formula Li d A 1 x A 2 y (TO 4 ) z Garnet (A 1 A is a cation with oxidation degree +II. 2 is a cation with oxidation degree +III, (TO 4 ) represents an anion, T is the atom with oxidation degree +IV located at the center of the tetrahedron formed by the oxygen atom, d is 2 to 10; x is 2.6 to 3.4; y is 1.7 to 2.3; z is 2.9 to 3.1; - Garnet to be selected from the following: Li 7 La 3 Zr 2 O 12 Li 6 La 2 BaTa 2 O 12 Li 5.5 La 3 Nb 1.75 In 0.25 O 12 Li 5 La 3 M 2 O 12 (M = Nb or Ta or a mixture of these two compounds); Li 7-x Ba x La 3-x M 2 O 12 (0 ≤ x ≤ 1 and M = Nb or Ta or a mixture of these two compounds); Li 7-x La 3 Zr 2-x M x O 12 (0 ≤ x ≤ 2 and M = Al, Ga, Ta, or a mixture of two or three of these compounds); - Lithium phosphate; - Lithium borate; - Oxynitride; -Li x PO y N z A lithium compound called "LiPON" is based on lithium oxynitride and phosphorus, expressed as (x ~ 2.8 and 2y + 3z ~ 7.8 and 0.16 ≤ z ≤ 0.4). w PO x N y S z (2x+3y+2z=5=w) or compound Li w PO x N y S z (3.2 ≤ x ≤ 3.8, 0.13 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.2, 2.9 ≤ w ≤ 3.3), or Li t P x Al y O u N v S w Compounds of the form (5x + 3y = 5, 2u + 3v + 2w = 5 + t, 2.9 ≤ t ≤ 3.3, 0.84 ≤ x ≤ 0.94, 0.094 ≤ y ≤ 0.26, 3.2 ≤ u ≤ 3.8, 0.13 ≤ v ≤ 0.46, 0 ≤ w ≤ 0.2); - Materials based on lithium phosphate or boronitride, referred to as "LiPON" and "LIBON," respectively; - Lithium compounds based on lithium, phosphorus, and silicon oxynitride, known as "LiSiPON"; -LiBON, LiSiON, LiSON, Thio-LiSiOCON, LiPONB-type lithium oxynitrides (B, P, and S represent boron, phosphorus, and sulfur, respectively); -(1-x)LiBO 2-x Li 2 SO 4 LiBSOs including (0.4 ≤ x ≤ 0.8); - Lithium oxide; - Silicates; - Antiperovskite type solid electrolyte selected from the following: Li 3 OA (where A is a halogen atom or a mixture of halogen atoms, at least one of the elements selected from F, Cl, Br, and I, or a mixture of two, three, or four of these elements); Li (3-x) M x/2 OA (0 < x ≤ 3, M is a divalent metal, A is a halogen atom or a mixture of halogen atoms, and at least one element selected from F, Cl, Br, I or a mixture of two, three, or four of these elements); Li (3-x) M 3 x/3 OA (0≦x≦3, M 3 (where A is a trivalent metal, A is a halogen atom or a mixture of halogen atoms, and at least one element selected from F, Cl, Br, I or a mixture of two, three, or four of these elements); or LiCOX z Y (1-z) (X and Y are halogen atoms as described above with respect to A, and 0 ≤ z ≤ 1); - Compound La 0.51 Li 0.34 Ti 2.94 , Li 3.4 V 0.4 Ge 0.6 O 4 , Li 2 O-Nb 2 O 5 , LiAlGaSPO 4 ; -Li 2 CO 3 , B 2 O 3 , Li 2 O, Al(PO 3 ) 3 LiF, P 2 S 3 , Li 2 S, Li 3 N, Li 14 Zn(GeO 4 ) 4 , Li 3.6 Ge 0.6 V 0.4 O 4 , LiTi 2 (PO 4 ) 3 , Li 3.25 Ge 0.25 P 0.25 S 4 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , Li 1+x Al x M 2-x (PO 4 ) 3 (M=Ge, Ti and / or Hf and 0<x<1), Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0≦x≦1 and 0≦y≦1) based compound.

2. The manufacturing method according to claim 1, wherein the non-aggregated nanoparticles of the material P having the first size D1 account for 50% to 75% of the total mass of the nanoparticles.

3. The manufacturing method according to claim 1, wherein the Dv50 value of the second size D2 nanoparticle is at least one-twelfth of the Dv50 value of the first size D1 nanoparticle.

4. The manufacturing method according to claim 1, characterized in that a suspension of non-aggregated nanoparticles of the material P is obtained using a monodisperse suspension of nanoparticles of the material P having the first size D1.

5. The manufacturing method according to claim 1, characterized in that the suspension of nanoparticles of the material P having the second size D2 is obtained using a monodisperse suspension.

6. The manufacturing method according to claim 1, characterized in that the deposition of the dense layer is carried out by electrophoresis, dip coating, inkjet printing, roll coating, curtain coating, or doctor blade.

7. The manufacturing method according to claim 1, characterized in that the suspension has a viscosity of 20 cP to 2000 cP as measured at 20°C.

8. The aforementioned garnet is given by formula Li d A 1 x A 2 y (TO 4 ) z It has A 1 is selected from Ca, Mg, Sr, Ba, Fe, Mn, Zn, Y, or Gd, A 2 is selected from Al, Fe, Cr, Ga, Ti or La, (TO 4 The method for producing the product according to claim 1, wherein ) is a silicate anion or a zirconate anion.

9. Formula Li d A 1 x A 2 y (TO 4 ) z The manufacturing method according to claim 1, wherein all or part of the garnet having an oxidation degree of +IV T is substituted with an atom having an oxidation degree of +III or +V.

10. - Lithium phosphate is a NaSiON type lithium phosphate, Li 3 PO 4 LiPO 3 Li represented as "LASP" 3 Al 0.4 Sc 1.6 (PO 4 ) 3 Li 1.2 Zr 1.9 Ca 0.1 (PO 4 ) 3 ;LiZr 2 (PO 4 ) 3 Li 1+3x Zr 2 (P 1-x Si x O 4 ) 3 (1.8<x<2.3);Li 1+6x Zr 2 (P 1-x B x O 4 ) 3 (0≦x≦0.25);Li 3 (Sc 2-x M x ) (PO 4 ) 3 (M = Al or Y and 0 ≤ x ≤ 1); Li 1+x M x (Sc) 2-x (PO 4 ) 3 (M = Al, Y, Ga or a mixture of the three compounds and 0 ≤ x ≤ 0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (PO 4 ) 3 (0 ≤ x ≤ 0.8; 0 ≤ y ≤ 1 and M = Al or Y or a mixture of these two compounds); Li 1+x M x (Ga) 2-x (PO 4 ) 3 (M = Al, Y, or a mixture of these two compounds, and 0 ≤ x ≤ 0.8); Li represented as "LATP" 1+x Al x Ti 2-x (PO 4 ) 3 (0 ≤ x ≤ 1); or Li represented by "LAGP" 1+x Al x Ge 2-x (PO 4 ) 3 (0 ≤ x ≤ 1); or Li 1+x+z M x (Ge 1-y Ti y ) 2-x Si z P 3-z O 12 (0 ≤ x ≤ 0.8 and 0 ≤ y ≤ 1.0 and 0 ≤ z ≤ 0.6 and M = Al, Ga, or Y or a mixture of two or three of these compounds); Li 3+y (Sc 2-x M x ) Q y P 3-y O 12 (M = Al and / or Y and Q = Si and / or Se, 0 ≤ x ≤ 0.8 and 0 ≤ y ≤ 1); or Li 1+x+y M x Sc 2-x Q y P 3-y O 12 (M = Al, Y, Ga or a mixture of these three compounds, Q = Si and / or Se, 0 ≤ x ≤ 0.8 and 0 ≤ y ≤ 1); or Li 1+x+y+z M x (Ga 1-y Sc y ) 2-x Q z P 3-z O 12 (0 ≤ x ≤ 0.8, 0 ≤ y ≤ 1, 0 ≤ z ≤ 0.6, M = Al or Y or a mixture of these two compounds, Q = Si and / or Se); or Li 1+x Zr 2-x B x (PO 4 ) 3 (0 ≤ x ≤ 0.25); or Li 1+x Zr 2-x Ca x (PO 4 ) 3 (0 ≤ x ≤ 0.25); or Li 1+x M 3 x M 2-x P 3 O 12 (0 ≤ x ≤ 1 and M) 3 =Cr, V, Ca, B, Mg, Bi and / or Mo, M = Sc, Sn, Zr, Hf, Se or Si or mixtures thereof); Li 1+2x Ca x Zr 2-x (PO 4 ) 3 (0 ≤ x ≤ 0.25); selected from, - Lithium borate is Li 3 (Sc 2-x M x ) (BO 3 ) 3 (M = Al or Y and 0 ≤ x ≤ 1); Li 1+x M x (Sc) 2-x (BO 3 ) 3 (M = Al, Y, Ga, or a mixture of these three compounds, and 0 ≤ x ≤ 0.8); Li 1+x M x (Ga 1-y Sc y ) 2-x (BO 3 ) 3 (0 ≤ x ≤ 0.8, 0 ≤ y ≤ 1 and M = Al or Y); Li 1+x M x (Ga) 2-x (BO 3 ) 3 (M = Al, Y, or a mixture of both compounds, where 0 ≤ x ≤ 0.8); Li 3 BO 3 Li 3 BO 3 -Li 2 SO 4 Li 3 BO 3 -Li 2 SiO 4 Li 3 BO 3 -Li 2 SiO 4 -Li 2 SO 4 ; selected from, -Oxynitrides are Li 3 PO 4-x N 2x/3 Li 4 SiO 4-x N 2x/3 Li 4 GeO 4-x N 2x/3 (0 < x < 4) or Li 3 BO 3-x N 2x/3 Selected from (0 < x < 3), - Lithium oxide is Li 7 La 3 Zr 2 O 12 or Li 5+x La 3 (Zr x A 2-x ) O 12 (A = Sc, Y, Al, Ga and 1.4 ≤ x ≤ 2), Li 0.35 La 0.55 TiO 3 or Li 3x La 2/3-x TiO 3 Selected from (0 ≤ x ≤ 0.16) (LLTO); - Silicates are Li 2 Si 2 O 5 Li 2 SiO 3 Li 2 Si 2 O 6 LiAlSio 4 Li 4 SiO 4 LiAlSi 2 O 6 A manufacturing method according to claim 1, selected from the following.

11. The nanoparticles of the material P include nanoparticles composed of a core and a shell of the material P. The manufacturing method according to claim 1, characterized by the following:

12. The manufacturing method according to claim 11, characterized in that the shell is formed of a material that is an electronic conductor.

13. The manufacturing method according to claim 11, characterized in that the shell is formed from a material that is an electronic insulator and a cation conductor.

14. A method for manufacturing a lithium-ion battery, comprising the steps of a method for manufacturing a dense layer as described in any one of claims 1 to 13.

15. The manufacturing method according to claim 14, wherein a porous layer intended to form a separator is also deposited.

16. The manufacturing method according to claim 15, wherein the porous layer is a mesoporous layer having a mesoporous volume of 25% to 75%.

17. The method for depositing the porous layer is selected from the group formed by the following, according to the manufacturing method of claim 15: Printing methods including electrophoresis, inkjet printing and flexographic printing, and coating methods including roll coating, curtain coating, doctor blade coating, slot die coating and dip coating, wherein in all cases deposition is carried out using a suspension of nanoparticle aggregates or clumps.

18. A colloidal suspension is used to deposit the porous layer comprising aggregates or clumps of nanoparticles of at least one inorganic material having a median primary diameter Dv50 of 2 nm to 100 nm, The manufacturing method according to claim 15, wherein the aggregate or mass has a median primary diameter Dv50 of 50 nm to 300 nm.

19. The manufacturing method according to claim 17, wherein the obtained layer is dried and compacted by pressurization and / or heating to obtain the porous layer.

20. The manufacturing method according to claim 15, wherein the porous layer is deposited on the dense layer.

21. The manufacturing method according to claim 15, wherein the dense layer is deposited on the porous layer.

22. The manufacturing method according to claim 15, wherein the porous layer is impregnated with a mobile lithium ion carrier liquid selected from the group formed by the following: • An electrolyte composed of at least one aprotic solvent and at least one lithium salt; • An electrolyte composed of at least one ionic liquid or ionic polyliquid and at least one lithium salt; A mixture of at least one aprotic solvent, at least one ionic liquid or ionic polyliquid, and at least one lithium salt; - A polymer made ionically conductive by adding at least one lithium salt; and A polymer made ion-conductive by adding a liquid electrolyte in either a polymer phase or a mesoporous structure.

23. A dense layer prepared by the method described in claim 1.

24. The dense layer according to claim 23, characterized in that it is selected from the anode, cathode, or electrolyte of an electrochemical device.

25. An electrochemical device comprising at least one dense layer as described in claim 23 or 24.

26. The electrochemical device according to claim 25, characterized in that it comprises a battery.

27. The electrochemical device according to claim 26, characterized by comprising an anode and / or cathode which is a dense layer as described in claim 23 or 24.

28. The electrochemical device according to claim 26 or 27, characterized by comprising an electrolyte layer which is a dense layer as described in claim 23 or 24.

29. The electrochemical device according to claim 27, characterized in that it includes an electrolyte solution immersed in a porous separator that separates the anode and the cathode.

Citation Information

Patent Citations

  • Cathode active material, its manufacturing method and cathode as well as lithium cell using the material

    JP2006228733A

  • Coating liquid for positive electrode formation for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    JP2009146788A

  • Method for manufacturing solid electrolyte thin films for lithium-ion batteries

    JP2014535141A

  • Method for manufacturing high-density thin films by electrophoresis

    JP2015504478A

  • Nanoporous composite separator with enhanced thermal conductivity

    JP2016517161A